A Case Study Of Kapar Power Station - Haron, Azlan (2009)
This case study focuses on examining the impact of privatisation on Kapar Power Station, the largest power plant in Malaysia in pursuit of the evidence that privatisation has led to improved efficiency. The argument is explored by consulting and reviewing written documents and literatures and by drawing together some of the important research that has been undertaken on the privatisation issue in order to improve the understanding of reformation processes in general and in the context of Malaysia and thereby shall contribute to the design of better reform programmes.